Captured : the Japanese internment of American civilians in the Philippines, 1941-1945 - Cogan, Frances B. (University of Georgia Press, 2000)
Cogan explores the daily life in the five major internment camps held by Japan during its occupation of the Philippines, in which more than five thousand American civilians were held between 1941 and 1945.